Aboriginal heritage as ecological proxy in south-eastern Australia: a Barapa wetland village. Issue 1 (2nd January 2021) - Pardoe, Colin; Hutton, Dan
ABSTRACT: Aboriginal archaeology has a central role to play among the myriad government agencies and professional disciplines involved in land and water management of the Murray River Basin in south-eastern Australia. In this study, we examine managed water flows against the archaeological record which provides secure evidence of how people lived at the Murray River floodplain wetlands before European colonisation. Seasonal residential patterns and economic activities of large populations have been reconstructed using archaeological, environmental, and hydrological information. The result is a picture of people living in large groupings – villages and hamlets – around water bodies that we suggest are ecological 'hot spots' within the forest. In identifying the preferred locations of village sites, we present the case for modification of environmental water delivery from large area forest flooding to targeted smaller water bodies that form ecological hot spots throughout the river floodplain landscape. Traditional Aboriginal land use in the form of the distribution of Aboriginal sites can act as an environmental proxy to inform heritage, land and water management policy and practices that seek to restore the health of the Murray River.